Evaluating metabolic changes in H9c2 cardiomyoblasts exposed to LPS: Towards understanding sepsis mechanisms - Amandine Szczesnowski; Karine Pichavant-Rafini; Marie-Dominique Jezequel; Michaël Théron; Karelle Léon (PLoS ONE, 2025)
Sepsis is a major public health concern associated with high mortality rates, particularly due to sepsis-induced myocardial dysfunction (SIMD), which affects about 50% of septic patients. This study investigates how mitochondrial dysfunction contributes to SIMD by examining metabolic changes in H9c2 cardiomyoblasts exposed to varying concentrations of lipopolysaccharide (LPS), a bacterial endotoxin, to enhance our understanding of the relationship between infection severity and metabolic responses. H9c2 cells were treated with LPS at concentrations of 0.5, 1, 2.5, and 5 µg/mL for 24 or 48 hours. Cell viability was measured using the MTT assay, and gene expression related to inflammation and mitochondrial function was analyzed through Real-Time PCR. Mitochondrial respiration and energy metabolism were assessed using the Seahorse MitoStress kit. Results showed that while 2.5 and 5 µg/mL of LPS for 24 hours did not significantly impact cell viability, exposure to 5 µg/mL for 48 hours led to a 77.7% decrease in survival. Gene analysis indicated significant overexpression of IL-6 and SOD2, with consistent underexpression of mt-ND1. Mitochondrial respiration increased at lower LPS concentrations but decreased at 5 µg/mL. Glycolytic metabolism also increased at lower LPS levels but decreased at higher concentrations. Inhibition of metabolic pathways affected mitochondrial function, especially at higher LPS concentrations. Our findings suggest that LPS induces metabolic disturbances in H9c2 cells, with adaptive responses at lower concentrations. However, excessive exposure results in mitochondrial and cellular damage, decreasing overall metabolism.